INVESTIGATION AND IMPLEMENTATION OF JENKINS PIPELINES INTO RASPBERRY PI FOR AUTOMATED CONTROL UNITS - Havran, Volodymyr; Orynchak, Maria (Collection of scientific papers «ΛΌГOΣ», 2022)
Introduction. Mowing toward innovations means delivering new devices, technologies and software on a daily basis. To fastly react to the rapid changes, the development methodology CI/CD play a key role.